IKLIM KOMUNIKASI ORGANISASI DAN SEMANGAT KERJA PARA PERSONIL POLRI DI POLWIL SURAKARTA - Hastasari, Chatia (KOMUNITAS, 2014)
POLRI hasÂ hierarchyÂ organizationÂ same withÂ otherÂ militaryÂ institution. The occupationÂ placementÂ basedÂ onÂ levelÂ ofÂ promotion,Â higherÂ positionÂ ofÂ the POLRIâs promotion increase their occupation and their welfare. However, the higher level of lobby to the leader will determine the occupation, because not all occupation in police can increase the welfare of their personnel. This is the cause of polemic in police institution. The purposeof this research is to know the significant relation between organizational communication condition and working spirit of the POLRIâs personnel in POLWIL Surakarta and to know the significant relation between social economy status and the organizational communicationÂ conditionÂ andÂ workingÂ spiritÂ ofÂ theÂ PolriâsÂ personnelÂ in POLWIL Surakarta. The type of this research is explanatory research thet will explainÂ theÂ causalÂ relationÂ betweenÂ itsÂ variableÂ throughÂ hypothesis examination.Â TheÂ researchÂ usedÂ surveyÂ methodÂ thatÂ takeÂ sampleÂ from population and uesd questioner as the primary dataÂ collector. The research take 76 sample use Yamane formula. There are 3 variables where the relation betweenÂ independentÂ variableÂ (organzationalÂ communication condition)Â and dependentÂ variableÂ (workingÂ spirit)Â willÂ beÂ presentedÂ byÂ thirdÂ variableÂ that will be controled its effect (social economy status), so the writer used Kendall partial correlation coefficient. Based on the wholedata analysis result, it can beÂ concludedÂ thatÂ amongÂ theÂ threeÂ variablesÂ namely, organzational communicationÂ conditionÂ (X),Â workingÂ spiritÂ (Y)Â and socialÂ economyÂ status (Z), the result is 0,752. the early value of Txy was 0, 765 and after the effect was controlled by social economy status (Z) becomes0, 752. so, it decrease about 0, 013. it means that social economy status is not the particular things thatÂ effectÂ theÂ communicationÂ conditionÂ andÂ working spiritÂ ownedÂ byÂ the personnel of POLRI in POLWIL Surakarta. Keywords: Organizational communication, organizational communication condition, and working spirit